What does it mean when A(dot)(B x C) = -A(dot)(B x C)?
I met with a tutor today and she said that since LHS = -(LHS) then these vector expressions must both be equal to zero.
Did some googling but can't find why this is so. Thanks in advance.
This was a problem on my exam which stated that we were to assume that LHS was indeed equal to the RHS, that is LHS = -(LHS). So it was incorrect to simply say that "LHS is not equal to the RHS" which is why I got the problem wrong.
- alexLv 72 years agoBest Answer
LHS = -(LHS)
LHS + (LHS) = 0
2(LHS) = 0
LHS = 0
- nbsaleLv 62 years ago
Why google it? Just work it out, since it's very straightforward.
Let A = <a_i> and BXC = <d_i>
Then the dot products give you
sum (a_i times d_i) = k
sum (-a_i time d_i) = -k but that = k also.
k = -k
Add k to both sides:
2k = 0
divide by 2
k = 0
- ComoLv 72 years ago
A • ( B x C ) + A • ( B x C ) = 0
A • ( B x C ) = 0
- VamanLv 72 years ago
Since sum is 0 we can stay that A is perpendicular to BxC. Here A, B C should be vectors.
- How do you think about the answers? You can sign in to vote the answer.
- Jeffrey KLv 62 years ago
If vectors A, B, C are in the same plane, then this expression is zero. B x C yields a vector perpendicular to the plane that B and C lie in. The dot product of perpendicular vectors is zero.
So A . B x C = 0